Improving the diameters of interferometric calibrators with MATISSE. Issue 1 (17th November 2021) - Robbe-Dubois, S; Cruzalèbes, P; Berio, Ph; Meilland, A; Petrov, R-G; Allouche, F; Salabert, D; Paladini, C; Matter, A; Millour, F; Lagarde, S; Lopez, B; et al.
ABSTRACT: A good knowledge of the angular diameters of stars used to calibrate the observables in stellar interferometry is fundamental. As the available precision for giant stars is worse than the required per cent level, we aim to improve the knowledge of many diameters using MATISSE (Multiple AperTure mid-Infrared SpectroScopic Experiment) data in its different instrumental configurations. Using the squared visibility MATISSE observable, we compute the angular diameter value, which ensures the best-fitting curves, assuming an intensity distribution of a uniform disc. We take into account that the transfer function varies over the wavelength and is different from one instrumental configuration to another. The uncertainties on the diameters are estimated using the residual bootstrap method. Using the low spectral resolution mode in the L band, we observed a set of 35 potential calibrators selected in the Mid-infrared stellar Diameter and Flux Compilation Catalogue with diameters ranging from about 1 to 3 mas. We reach a precision on the diameter estimates in the range 0.6 per cent to 4.1 per cent. The study of the stability of the transfer function in visibility over two nights makes us confident in our results. In addition, we identify one star, 75 Vir initially present in the calibrator lists, for which our method does not converge, and prove to be a binary star. This leads us to the conclusion that our method is actually necessary to improve the quality of the astrophysical results obtained with MATISSE, and that it can be used as a useful tool for 'bad calibrator' detection.